Photo-sensitive hybrids constructed from diphenyliodonium and metal-thiocyanates: photo-induced structure and property transformations. Issue 6 (19th January 2022) - Song, Kai-Yue; Yang, Zhen-Cong; Zhou, Pan-Ke; Zong, Lu-Lu; Li, Hao-Hong; Jiang, Rong; Chen, Zhi-Rong
Abstract : New hybrids constructed from diphenyliodonium and metal thiocyanates have been prepared, and their photo-induced structural transformations and corresponding color/fluorescence/magnetism variations have been investigated. Abstract : Strong electron-poor cation diphenyliodonium was firstly incorporated with transition metal thiocyanates to obtain three new photo-sensitive hybrids, (DPI)3 [Mn(SCN)5 (H2 O)]·0.25H2 O (α- 1 ), {(DPI)2 [Ni(SCN)4 ]} n (α- 2 ) and {(DPI)6 [Cd3 (SCN)12 ]} n (α- 3 ) (DPI + = diphenyliodonium), whose photo-induced structural transformations to corresponding β-phases have been disclosed. After irradiating, all the MX6 octahedrons stretch clearly along the M–S directions, and C–H⋯π interactions and the secondary hypervalent I(iii )⋯S halogen bonds are weakened. The hydrogen bonds are also weakened, except for those in 1 . Time-dependent solid-state UV-vis spectra, PXRD patterns and EPR spectra before and after irradiating were obtained to prove the irreversible structural transformations of the hybrids, during which minor structural adjustments occurred. Consequently, the fluorescence emission changed from blue (α- 3 ) to yellow (β- 3 ) upon irradiation. Interestingly, obvious photomagnetization on 1 with a χ M T increase of 14.89% and photodemagnetization on 2 with a χ M T decrease of 12.82% can be observed. Finally, these hybrids can be used as long-term inkless and erasable print media. This work demonstrates the potential application of diphenyliodonium-based hybrids in some photo-sensitive functional materials.